Riluzole: What It Does to Spinal and Brainstem Neurons and How It Does It. (April 2013) - Cifra, Alessandra; Mazzone, Graciela L.; Nistri, Andrea
Amyotrophic lateral sclerosis (Lou Gehrig's disease) is a devastating neurodegenerative disorder for which the only licensed treatment is riluzole. Although riluzole clinical efficacy is rather limited, its use has important implications for identifying those parameters that might improve its clinical benefits (dose, timing, disease stage) and for its off-label administration in other neurodegenerative diseases, such as spinal cord injury. Studies of riluzole also have an intrinsically heuristic value to unveil mechanisms regulating the excitability of brain and spinal neurons because this drug is a pharmacological tool to probe the function of certain ion channels, or to study neurotransmitter release processes, and intracellular neuroprotective pathways. The present review focuses on how riluzole acts on brain and spinal neurons within motor networks, what mechanisms can be deduced from its effects, and what conditions may favor its use to contrast neurodegeneration or to ameliorate late symptoms like spasticity. Taking as an example the experimental neurodegeneration caused by overactivation of glutamatergic synapses (excitotoxicity), it seems likely that protection of motor networks by riluzole involves selected administration timing and dosing to target processes for releasing glutamate from very active synapses or for dampening repetitive firing by hyperfunctional motor cells.